KECUKUPAN ENERGI PROTEIN PADA ANAK-ANAK (24-59 BULAN) DI INDONESIA - Noviati Fuada; Tjetjep S Hidayat (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2015)
Introduction. Poverty causes people to have a limitation in the supply of food needed to meet energy and protein adequacy for families including children under five. Method. Sample is children ages 24-59 months toddler. Number of samples 11690 (Riskesdas 2010), which can be analyzed along with 6796 consumption data. Deficient in energy consumption occur if <80% rate of nutrient adequacy (RDA) which is recommended by age group, whereas the protein deficit when <80% RDA. Results. Based on the average percent of the consumption of energy and protein to RDA ( recommended adequacy rate ) found the energy as much as 101.8%, and protein to 142.9% in urban and 93.1% average energy, and 126.8% of protein in rural areas, with the Kruskal-Wallis difference was significant at p=0.000. however was found also by grouping according to the percent of the average age of the energy adequacy of the recommended protein that is between the age group 24-35 months for 99.4% of energy, and protein 139.4%. In the age group 36-47 months 101.9% of energy, and protein 141.1%. While in the 48-59 month age group 88.9% of energy, and 122.1% protein. Conclusion. the mean of the consumption of energy, protein and fat children aged 24-59 months in urban areas than in rural areas superiors. The toddler age group 48-59 months has energy consumption, and low protein than other groups. Recommendation. Children 48-59 months of age, is the age of the growth and development of intelligence. Necessary, coordination of action across programs, such as health promotion, cash transfers (BLT Programme), education curriculum, and others, can load messages Nutrition Guide for Balance